PERILAKU KONSUMEN TERHADAP PEMAKAIAN JAMU CAP NYONYA MENEER DI KOTAMADYA BENGKULU - Ermy Wijaya (UNIVED Press, 2017)
Ermy Wijaya ; The aim of this study is to determine is there any significant relationship between the outside behavior variables of consumers to the consumption rate of Jamu Cap Nyonya Meneer and is there influence of inside behavior variables of consumer to the consumption rate of Jamu Cap Nyonya Meneer. Gading Cempaka Subdistrict Bengkulu City is a research area that is selected with the population of research is the households that live in Bengkulu City. The sample was carried out based on specific criteria, i.e all households classified as mature or aged 15 years and above. From the population were classified into five villages, each village elected were taken as sample. The result gained from the study was as follows: age level as a variable behavior has influence on consumers’ behavior to the consumption rate of Jamu Cap Nyonya Meneerin accordance with the age level. Where, at the age of 15-19 tends to consume Jamu Cap Nyonya Meneerat least once, at the age of 20 - 50 and above tends to consume Jamu Cap Nyonya Meneerincreases. From the test results showed a statistically significant relationship between the levels of education as outside behavior variable to the consumers’ behavior of Jamu Cap Nyonya Meneer. The level income ofoutside behavior variables has significant relationships on consumers’ behavior of Jamu Cap Nyonya Meneer.Key Words : Consumers’ Behavior, Level Of Consumstion.